Effect of BAP and Picloram on Shoot Induction (Musa acuminata Colla var. Mulu Bebek) - Arief, Nurul Huda Am Zen; Rahayu, Enni Suwarsi; Pa’ee, Furzani; Habibah, Noor Aini (Universitas Negeri Semarang, 2025)
Musa acuminata Colla var. Mulu Bebek is a high-quality banana from Ternate, North Maluku. Its conventional cultivation faces challenges due to Fusarium wilt, reducing productivity. In vitro culture offers a solution for rapid, disease-free seedling production. This study aims to examine the effect of BAP and picloram on shoot induction using a CRFD at various concentrations (0–3 ppm) and evaluate the percentage of live explants, emergence time, and number and length of shoots and roots. Results show that 1 ppm picloram accelerates root emergence, while 0 ppm promotes the fastest shoot emergence, the longest shoot and root lengths. 1 ppm BAP increases shoot numbers. The interaction of picloram and BAP has a significant effect on the parameters of the fastest root emergence time, namely 1 ppm picloram + 0 ppm BAP, 1 ppm and 3 ppm, the fastest shoot emergence time, namely without the addition of PGR, and the longest shoot length, 0 ppm picloram + 2 ppm BAP. The combination of 0 ppm picloram + 1 ppm BAP is the optimal condition for a percentage of 100% live explants, the fastest time for root emergence, the highest number of shoots and roots, the longest shoot and root length and the optimal condition for the fastest time for shoot emergence is 0 picloram + 0 ppm BAP. This study provides insight into the role of BAP and picloram in inducing banana shoots that has not been reported before. The micropropagation media formula obtained in this study is an effort to improve the quality of healthy banana seedlings in the future.